On a corresponsive sport science - Woods, C.T.; Araújo, D.; Davids, K. (Sports Medicine, 2024)
In our societally extractive age, sport science risks being swept up in the intensifying desire to commodify the experiences of those that scientists proclaim to study. Coupled with the techno-digital revolution, this stems from a vertical (onto)logic that frames the sporting landscape as a static space filled with discrete objects waiting for us to capture, analyse, re-present and sell on as knowledge. Not only does this commodification degrade primary experience in the false hope of epistemological objectivity, it reinforces the unidirectionality of extractivism by setting inquirer apart from, and above of, inquiry. Here, we advocate for a different, more sentient logic grounded in the relationality of gifting as understood in indigenous philosophies. This foregrounds an ecological orientation to scholarship that sets out neither to objectify or describe that which is of concern, but to correspond with its becoming. On this, there are three threads we cast forward. First, in a corresponsive sport science, inhabitants are not objects of analysis, but lines in-becoming, who in answering to others, form knots in a meshwork. These knots constitute communal places in which inhabitants have joined with the differentiating coming-into-being of others. Second, knowledge is not authoritatively (re)cognitive, but humbly ecological; not produced vertically through imposition, but grown longitudinally in responsively moving from place to place. Third, research does not follow a vertically extractive (onto)logic, but is a practice of participant observation. This perspective appreciates that we, sport scientists, are also lines in-becoming that form parts of the knots in which we seek to know. In coda, our thesis is not a call for more qualitative or applied research in the sport sciences. It is a call to response-ably open up to that which sparks our curiosity, answering to what is shared with care, sensitivity and sincerity.